Hemodynamically significant patent ductus arteriosus and tissue oxygenation in preterm infants - Amaliah, Lissaberti; Indrayady, Indrayady; Ramadanti, Afifa; Nova, Ria; Akbari, Atika (Indonesian Pediatric Society, 2025)
Background One of the most common side effects of preterm birth is hemodynamically significant patent ductus arteriosus (hsPDA), with a prevalence of approximately 70% among preterm infants. The clinical consequences of hsPDA are impaired tissue perfusion and oxygenation to organs. Near-infrared spectroscopy (NIRS), a validated non-invasive method for determining regional oxygen saturation (rSO2), can identify early changes in organ perfusion and oxygenation. Cerebral and renal tissues as these vital organs are highly susceptible to systemic hypoperfusion caused by hsPDA, which can lead to serious complications such as brain injury and renal insufficiency. We used (NIRS to clarify the impact of hsPDA on regional oxygenation in the brains and kidneys of preterm infants. Objective To compare oxygenation of cerebral and renal regional tissues in preterm infants with and without hsPDA Methods A cross-sectional study was conducted at Mohammad Hoesin Hospital. Forty preterm infants (gestational age <37 weeks), born between November 2023 and September 2024, who were diagnosed with PDA and had a chronological age >24 hours and <7 days, were enrolled. Infants with multiple congenital anomalies, ductal-dependent cyanotic congenital heart disease, early-onset sepsis, or without parental consent were excluded. Cerebral and renal oxygenation were assessed using NIRS monitoring. Statistical analysis was performed with unpaired T-test. Results Based on echocardiographic criteria, 22 of the 40 infants had hsPDA, while 18 had non-hsPDA. The mean cerebral rSO2 values in the hsPDA and non-hsPDA groups were 79.5 (SD 12.1)% and 80.9 (SD 4.3)%, respectively. The mean renal rSO2 values were 70.4 (SD 17.8)% and 77.8 (SD 6.4)%, respectively. The mean cerebral fractional tissue oxygen extraction (FTOE) values of the hspda and non-hsPDA groups were 0.2 (0.1 to 0.21). The mean renal FTOE values were 0.3 (SD 0.19) and 0.2 (SD 0.07), respectively. There were no significant differences between the two groups in renal and cerebral rSO2 and FTOE. Conclusion Preterm infants’ cerebral and renal tissue oxygenation is were not significantly different in those with and without hsPDA.